Effect of Compensation/ Pay on Staff Retention in Selected Commercial Banks in Adamawa State, Nigeria - John, Dr Ldama; Teru, Dr Peter (International Journal of Scientific Research and Management (IJSRM), 2017)
This study assessed compensation/pay and staff retention in selected commercial banks in Adamawa state. Thebed rock of this study was that inability to retain staff is bedevilling the Nigeria’s banking institutions.Therefore, the question of whether compensation/pay significantly affect retention of commercial bank staff isthe arena of the study. Data were collected from 197 bank staff from Yola north, Yola south, Mubi north andNuman local government areas using both close and open ended questionnaires. The data was analysed usingregression analysis, while Likert scale technique was used as measurement instrument for the study.Cronbach’s Alpha test was used to measure the reliability of the measurement instrument, which showed aresult of 77.4% reliability. The result shows that, a 1% increase in payment of monetary benefits (RPM),increased staff retention by 0.688, a 1% increase in the thirteenth month salaries (TMS), increased staffretention by 0.484, a 1% increase in timely payment of salaries (TPS), led to an increased staff retention by1.866, but a 1% increase in the use of money as an incentive (MMW), triggered a 0.155 decrease in staffretention. Findings of the study therefore revealed that compensation/ pay has positive effect on the retention ofcommercial bank staff, except when used as an incentive. The study therefore recommended that while usingcompensation/pay as motivational strategies, commercial banks’ management should avoid the use ofcompensation/pay as incentives